Mechanical Properties of Arecanut and GFR Hybrid Polypropylene Composites. (16th May 2022) - Rao, Yarrapragada K. S. S.; Ahmad, Ayaz; Battula, Sudheer Kumar; Alharbi, Reem Mohammed; Abdel-Raouf, Neveen; Ibraheem, Ibraheem Borie M.; Sholkamy, Essam Nageh; Bala, B. M.; Jenish, I.
Abstract : The mechanical characteristics of hybrid polypropylene composites may be enhanced by adjusting the fibre loading and ratio, according to this study. The hot press technique was utilised to generate a variety of composites with four different amounts of fibre loading. In addition, the fibre ratio in composites with a 20-weight-percent fibre loading was changed. The composites were characterised using Fourier transform infrared analysis as well as tensile, flexural, and hardness tests. In the composites that have been created, Fourier transform infrared examination showed that hemicelluloses, lignins, and moisture were present, all of which have the potential to reduce tensile strength. Fibre loading resulted in a decrease in tensile strength but an increase in Young's modulus. With increasing fibre loading, flexural modulus and hardness rose, whereas flexural strength declined. The best mechanical qualities were found in a composite made primarily of arecanut and glass fibres, with a weight ratio of 1 : 3.